Comparative Study on Russian Current Stimulation Versus Faradic Current in Pain and Functional Outcome in Osteoarthritis Knee (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: This study was designed to inspect the effectiveness of a comparative study on Russian CurrentStimulation versus Faradic Current in pain and functional outcome in osteoarthritis knee. Russian current is themost commonly used electrical stimulation to improve muscle strength. Faradic current is effective in treatingmuscle spasms caused by inflammation and in lowering painPurpose: To compare the effectiveness of Russian current stimulation versus Faradic current using the KOOSscale.Materials and Methods: This experimental study has been conducted from November 2022 to April 2023.A totalof 196 adults were collected from APR physiotherapy center with OA knee have been selected using the inclusionand exclusion criteria. They have been split into 2 groups Group A (n=98) and Group B (n=98) were assigned.Group A got Russian current stimulation, whereas Group B received Faradic current and the KOOS scale was usedto evaluate the subjects. The treatments were given for 5 sessions per week and continued for 4 weeks.Results: The mean value of Russian current at the post-test was found to be higher than the mean value of Faradiccurrent with a p-value of
Keywords: Russian current stimulation, OA knee, KOOS scale, Faradic current.